Oil, macroeconomics, and forests: assessing the linkages - Wunder, Sven; Sunderlin, William D. (2004)
How does an oil boom affect the forest cover of tropical oil exporting-countries? Are they more or less likely than non-oil countries to experience forest loss? What macro-economic linkages and policies are decisive? This article summarises research on land-use changes in eight tropical developing countries. Our country-comparative approach reveals that the direct oil impacts on forests are unquestionably subordinate compared to oil's derived macroeconomic impact. In most cases, oil wealth indirectly but significantly comes to protect tropical forests. The core mechanism here is that oil rents cause 'Dutch Disease', decreasing the price-competitiveness of agriculture and logging, which strongly diminishes pressures for deforestation and forest degradation. But domestic policy responses to oil wealth are also vital determinants for the forest outcome. When governments use most oil wealth for urban spending sprees, this reinforces the core effect by pulling more labor out of land-using and forest-degrading activities. Yet, in extreme cases when boosting oil revenues finance large road-construction programs or frontier-colonization projects, the core forest-protective effect of oil wealth can be reversed. Repeated currency devaluation and import protection of heavily land-using domestic sectors also contribute to increased forest pressures. These conclusions have ample policy implications, reaching beyond the group of tropical oil countries. Other international capital transfers, like bilateral credits, aid or debt relief can have similar impacts. These measures will alleviate pressures on forests, unless they come to bolster specific forest-detrimental policies. This also provides some suggestions on what forest-friendly safeguards could realistically be taken in the design of structural adjustment programs, considering the important trade-offs between development and conservation objectives.